2010
DOI: 10.1111/j.1464-5491.2010.03183.x
|View full text |Cite
|
Sign up to set email alerts
|

HbA1c in diagnosing and predicting Type 2 diabetes in impaired glucose tolerance: the Finnish Diabetes Prevention Study

Abstract: Of those with diabetes diagnosis based on two oral glucose tolerance tests during the Diabetes Prevention Study follow-up, 60% would have remained undiagnosed if diagnosis had been based on HbA(1c) ≥ 6.5% (≥ 48 mmol/mol) criterion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
34
1
4

Year Published

2011
2011
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 22 publications
6
34
1
4
Order By: Relevance
“…The authors give a study example where it was found that the standard HbA1c rule missed more than 60% of cases of early T2DM identified by IGT. [54] This may explain the jutted out portion of the classification accuracy vs HbA1c profile in Figure 5 in the vicinity of the proper maximum. That is, the standard HbA1c rule or the one based on IFG was often solely relied on to determine the T2DM status.…”
Section: T2dm Disease Clustermentioning
confidence: 99%
“…The authors give a study example where it was found that the standard HbA1c rule missed more than 60% of cases of early T2DM identified by IGT. [54] This may explain the jutted out portion of the classification accuracy vs HbA1c profile in Figure 5 in the vicinity of the proper maximum. That is, the standard HbA1c rule or the one based on IFG was often solely relied on to determine the T2DM status.…”
Section: T2dm Disease Clustermentioning
confidence: 99%
“…In the Rancho Bernardo study, 85% of participants with A1C ≥ 6.5% were not classified as diabetic by ADA criteria and onethird of the participants with diabetes by ADA criteria would be classified as normoglycemic by A1C, i.e., a significant proportion of misclassification [25]. Analysis of U.S. National Health and Nutrition Examination Survey (NHANES) data revealed that 50-60% of patients with FPG ≥ 7 mmol/l had A1C < 6.5%, suggesting that A1C might reduce the number of people diagnosed as having diabetes compared to the current glycemic criteria in use [28,43].…”
Section: Resultsmentioning
confidence: 99%
“…Jako badanie diagnostyczne w rozpoznawaniu cukrzycy zaleca się pomiar odsetka hemoglobiny glikowanej (HbA 1c ) [7,8], jednak nadal istnieją kontrowersje dotyczące czułości tego parametru w prognozowaniu ryzyka cukrzycy. Wartości HbA 1c wynoszą-ce < 6,5% nie wykluczają cukrzycy, która może zostać wykryta na podstawie oznaczenia stężenia glukozy we krwi [7][8][9][10], co opisano w części 3.3. Wyróżniono 4 podstawowe etiologiczne kategorie cukrzycy: cukrzycę typu 1, typu 2, "inne swoiste typy cukrzycy" oraz cukrzycę ciążową (tab.…”
Section: Sztokholm I Leeds Kwiecień 2013unclassified
“…W badaniu przeprowadzonym w Hiszpanii u osób z grupy dużego ryzyka [> 12/26 punktów w skali FINnish Diabetes RIsk SCore (FINDRISC)] stwierdzono na podstawie OGTT, że 8,6% uczestników miało nierozpoznaną cukrzycę, jednak tylko u 1,4% stężenie HbA 1c wynosiło > 6,5%, co wskazuje na potrzebę dalszej oceny użyteczności HbA 1c jako podstawowego testu diagnostycznego w określonych populacjach [9]. Nadal istnieją kontrowersje dotyczące stosowania HbA 1c do wykrywania nierozpoznanej cukrzycy u pacjentów z chorobą wieńcową i czynnikami ryzyka CVD [7][8][9][10]32], chociaż orędownicy tej metody argumentują, że stężenie HbA 1c w zakresie 6,0-6,5% wymaga zalecenia zmiany stylu życia i postępowania mającego na celu ograniczenie tego czynnika ryzyka oraz że dodatkowe informacje uzyskane w wyniku badania 2hPG nie spowodują zmiany postępowania.…”
Section: S 329unclassified